Learning organization as mediator between leadership communication, knowledge towards organizational commitment among academician in Chinese Higher Education Institutes - Zhengkang, Fang (2025)
Chinese Higher Education Institutions (HEIs) are under increasing pressure to compete globally through initiatives such as the Double First-Class policy. While previous studies have emphasized the importance of Leadership Communication (LC) and Knowledge Management (KM), little is known about how these factors interact through the mechanism of Learning Organization (LO) to strengthen Organizational Commitment (OC). The purpose of this study is to examine how Leadership Communication (LC) and Knowledge Management (KM) shape Organizational Commitment (OC) among academicians in Chinese Higher Education Institutions (HEIs), with the Learning Organization (LO) as a mediator. This study employed a quantitative design using a survey method to collect data from academicians in public universities in Guizhou, China. A structured questionnaire was developed to measure Leadership Communication (LC), Knowledge Management (KM), Learning Organization (LO), and Organizational Commitment (OC), with items adapted from validated scales in previous studies. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The analysis revealed that KM significantly influenced OC both directly and indirectly through LO, whereas LC affected OC only indirectly, thus confirming the mediating role of LO in this relationship. The findings showed that KM plays an important role in strengthening OC among academicians. KM not only has a direct effect on OC but also exerts an indirect influence through the development of a LO. In contrast, LC was found to affect OC only indirectly through LO, indicating that communication alone is insufficient to drive commitment unless embedded within a learning-oriented culture. These findings highlight LO as a mediator. This study emphasizes the role of the LO as the key link between LC, KM, and OC in Chinese HEIs. It extends the Knowledge- Based Theory by highlighting the importance of a learning culture and offers practical implications for strengthening faculty commitment and institutional resilience.